Frontispiece: Design Concepts for Solution and Solid‐State Emitters – A Modern Viewpoint on Classical and Non‐Classical Approaches. Issue 2 (9th January 2023) - Huber, Alexander; Dubbert, Justin; Scherz, Tim D.; Voskuhl, Jens
Abstract : Bridging a gap : Solution and solid‐state emitters (SSSEs) combine effective emission independently from their state of aggregation. In their Minireview on page  ff., J. Voskuhl et al. describe classification of SSSEs in classic and non‐classic examples.